Recovery of driving competence: an important target of therapy in mental disorders - Aschenbrenner, Steffen; Schale, A.; Weisbrod, Matthias; Laux, Gerd; Brunnauer, Alexander (Nervenheilkunde, 2013)
The driving competence in mental disorders is often restricted due to psychopathologic symptoms and cognitive impairments. This presents a major handicap for the reintegration of patients and is experienced both by those affected and clinicians as problematic. This paper presents diagnostic and treatment strategies taking into account the current legal situation and the potential conflicts concerning therapeutic relationships.